Optimization of the 9α-hydroxylation of steroid substrates using an original culture of Rhodococcus erythropolis - Andryushina, V. A.; Karpova, N. V.; Stytsenko, T. S.; Yaderets, V. V.; Voskresenskaya, E. D.; Dzhavakhia, V. V. (Regulatory Mechanisms in Biosystems, 2018)
To obtain inoculation material (cultivation stage 1), the biomass of Rhodococcus erythropolis VKPM AC-1740 was transferred from agar slants into 750 ml conic flasks containing 100 ml of vegetation media of the following composition (g/l): medium 1 – yeast extract, 10.0; glucose, 10.0; soybean flour, 10.0; КН2РО4, 2.0; Na2НРО4, 4.0 (рН 6.8–7.4); medium 2 – corn extract, 15.0; glucose, 10.0; КН2РО4, 2.0; Na2НРО4, 4.0 (рН 6.8–7.4). The culture was grown on a rotary shaker (220 rpm) for 68–72 h at 28–29 °С. To obtain a working biomass (cultivation stage 2), the inoculum obtained at the stage 1 was transferred into flasks containing the same media (the volume of seed material was 20% of the medium volume) and grown under the same conditions for 23–25 h. During a study of the effect of the inducer concentration on the rate of 9α-OH-AD formation, different concentrations (0.25, 0.50, and 1 g/l) of the AD solution in dimethylformamide (DMF) were added to the vegetation medium after 6 h of incubation. To perform AD transformation at a load of 5 g/l, 10 ml of Rh. erythropolis cells at the age of 23–25 h were transferred into 750 mL flasks with baffles containing 40 mL of vegetation medium supplemented with the steroid. AD was added in the form of microcrystals or suspension with a surfactant or DMF. The process was carried out at 28–29 ºC and with constant mixing (220 rpm). During AD transformation at a load of 10–30 g/l, the steroid was preliminarily precipitated from DMF solution. The resulting paste was mixed with a surfactant and transformation medium. The obtained homogeneous suspension was poured in equal amounts into the flasks with baffles, and then a concentrated cell mass was added (25 vol.%). To obtain a cell concentrate, cells were centrifuged for 1 h at 1500 rpm at the age of 23–25 h. The resulting biomass was homogenized, supplemented with a fresh medium to the required volume, and added into transformation flasks. The amount of a biomass required for AD transformation at a load of 10 g/l was 3.13 g/l (dry weight); in the case of a 30 g/l load, the biomass was added by two equal portions, and its total amount was 6.2 g/l (dry weight). The amount of 9α-OH-AD in a culture broth was evaluated by a thin-layer chromatography (TLC) and high-performance liquid chromatography (HPLC). Steroids were extracted by ethylacetate. To perform TLC, Sorbifil plates (Russia) and benzol: acetone mix (3 : 1) were used. HPLC was performed on a Gilson chromatographer (United States) equipped with a Silasorb C-18 column (10 μm, 4.0 × 250 mm); the flow rate was 0.8 ml/min. The mobile phase was МеОН : Н2О mix (70 : 30). The absorbance was measured at 260 nm. Replacement of corn extract, which has an unstable composition, by yeast extract and soybean flour and the use of glucose as an optimal carbon source for a Rh. erythropolis culture have provided a high-yield production of 9α-hydroxy-4-ene-3,17-dione with increased AD loads. Use of such techniques as the inoculum induction and application of surfactants have provided a positive effect on the AD transformation with a load exceeding 10 g/l. During 9α-hydroxylation of AD with a load of 30 g/l, a target product with the yield of 83% has been obtained.